New L-Serine Derivative Ligands as Cocatalysts for Diels-Alder Reaction. (5th December 2013) - Sousa, Carlos A. D.; Rodríguez-Borges, José E.; Freire, Cristina
Abstract : New L-serine derivative ligands were prepared and tested as cocatalyst in the Diels-Alder reactions between cyclopentadiene (CPD) and methyl acrylate, in the presence of several Lewis acids. The catalytic potential of the in situ formed complexes was evaluated based on the reaction yield. Bidentate serine ligands showed good ability to coordinate medium strength Lewis acids, thus boosting their catalytic activity. The synthesis of the L-serine ligands proved to be highly efficient and straightforward.